Mitogen-Activated Protein Kinase Phosphatase-2 Deletion Promotes Hyperglycemia and Susceptibility to Streptozotocin-Induced Diabetes in Female Mice In Vivo - Nabin Ghimire; Morgan Welch; Cassandra Secunda; Alexis Fink; Ahmed Lawan (Cells)
The development of type 2 diabetes (T2D) is largely dependent on the maintenance of pancreatic islet function and mass. Sexual dimorphism in T2D is evident in many areas, such as pathophysiology, treatment, and prevention. Mitogen-activated protein kinase phosphatase-2 (MKP-2) has a distinct role in the regulation of cell proliferation and the development of metabolic disorders. However, whether there is a causal relationship between MKP-2 and diabetes onset is unclear. The aim of this study was to determine the role of MKP-2 in the regulation of whole-body glucose homeostasis and the impact on pancreatic islet function using streptozotocin-induced pancreatic injury. Here, we show that female mice with whole-body deletion of MKP-2 exhibit hyperglycemia in mouse models treated with multiple low doses of streptozotocin (STZ). In comparison, both male MKP-2 wild-type and knockout mice were hyperglycemic. Consistent with the hyperglycemia, female MKP-2-deficient mice exhibited reduced islet size. Under T2D conditions, MKP-2-deficient mice display enhanced pancreatic JNK and ERK phosphorylation that is associated with the downregulation of genes important for pancreatic islet development and function, Pdx-1 and MafA. Furthermore, we found impaired metabolic flux in adipose tissue that is consistent with hyperglycemia and dysfunctional pancreas. MKP-2 deletion results in reduced Akt activation that is associated with increased adiposity and insulin resistance in female MKP-2 KO mice. These studies demonstrate the critical role of MKP-2 in the development of T2D diabetes in vivo. This suggests that MKP-2 may have a gender-specific role in diabetes development. This discovery raises the possibility that postmenopausal prevention of T2D may benefit from the activation of MKP-2 activity in islet cells.